L-T4 Therapy in Enteric Malabsorptive Disorders - Fallahi, Poupak; Ferrari, Silvia Martina; Elia, Giusy; Ragusa, Francesca; Paparo, Sabrina Rosaria; Antonelli, Alessandro (Frontiers in Endocrinology, 2021)
Levothyroxine (L-T4) absorption can be impaired by various causes: a) L-T4 ingestion during breakfast, or with food; b) conditions of reduced gastric acidity; c) intestinal procedures and diseases such as bariatric surgery, lactose intolerance (LI), celiac disease (CD), inflammatory bowel disease; d) drugs that alter L-T4 absorption, increasing the gastric pH, or preventing the dissolution of tablets. The development of new oral formulations, i.e. the liquid preparation and the soft gel capsule, represents the most recent advance regarding L-T4 therapy. Treating hypothyroidism with L-T4 tablets can lead to an improper control of thyroid-stimulating hormone (TSH) in 10-15% of patients. The improperly elevated TSH is usually managed by increasing the L-T4 daily dose, and revaluating TSH upon 2-6 months. The increase of the L-T4 dosage may cause iatrogenic hyperthyroidism, especially when the underlying disorders are cured. Liquid L-T4 can be administered in patients unable to swallow capsules or tablets, and this is one of its major benefits. Liquid L-T4 can: 1- overcome food and beverages interference; 2- bypass the malabsorption associated with an increased gastric pH; 3- circumvent the issue of malabsorption in patients who underwent bariatric surgery; 4-maintain TSH values under control better than L-T4 tablets in hypothyroid patients with typical or atypical CD, or in patients with LI. Few clinical studies evaluated soft gel L-T4 with encouraging findings in patients with gastric- or coffee-related malabsorption, or hypothyroid patients without malabsorption. Additional researches are necessary to investigate liquid L-T4, or soft gel capsule, in other conditions of altered L-T4 absorption.